20 solution proposals for the G20 - Dennis J. Snower; Dennis Görlich; Gianluca Grimalda; Matthias Lücke (Kiel Institute for the World Economy (IfW), 2017)
This report, by the co-chairs of the T20 process during Germany's G20 Presidency, presents 20 key policy recommendations for G20 policy-makers and stakeholders. The policy recommendations are formulated concisely to be easily accessible to those seeking a short summary of the main conclusions. Readers who are interested in the detailed recommendations are referred to the Policy Briefs in the G20 Insights Platform (www.g20-insights.org). This report includes only a selection of policy recommendations that have been chosen for their novelty, ease of implementation and relevance to the G20 during the German Presidency. The G20 Insights Platform contains the full range of T20 policy recommendations. – – Dieser Bericht, der von den Co-Chairs des T20-Prozesses (Think 20) während der deutschen G20-Präsidentschaft 2017 vorgelegt wurde, enthält 20 wichtige politische Empfehlungen für politische Entscheidungsträger und Interessengruppen rund um die G20. Die Politikvorschläge sind in Kurzform formuliert, um für diejenigen leicht zugänglich zu sein, die eine Zusammenfassung der wichtigsten Schlussfolgerungen suchen. Leser, die an den detaillierten Empfehlungen interessiert sind, werden auf die Policy Briefs auf der G20 Insights Plattform (www.g20-insights.org) verwiesen. Dieser Bericht enthält nur eine Auswahl von Politikempfehlungen, die aufgrund ihrer Neuartigkeit, ihrer einfachen Umsetzbarkeit und ihrer Relevanz für die G20 während der deutschen Präsidentschaft ausgewählt wurden. Die G20 Insights Plattform enthält die gesamte Bandbreite der T20-Politikempfehlungen.
Keywords: 330